Kyoto global consensus report onHelicobacter pylorigastritis: summary - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present basic issues of Helicobacter pylori gastritis that were covered during Kyoto consensus meeting. Key points. The panel of experts had discussed 22 questions, the answers to which resulted in formulation of 24 statements that were voted with estimation of degree of evidence, recommendation grade and consensus strength. Thus the consent rate has exceeded 80% for all statements. New classification of gastritis and duodenitis, based on the etiological approach has been proposed. It is recommended to qualify dyspepsia cases with sustained symptomatic improvement after successful eradication therapy as H. pylori-associated dyspepsia, and to distinguish them from functional dyspepsia. Broader application of magnification endoscopy methods is recommended for diagnostics of chronic gastritis. It is stressed, that the duly eradication therapy which is carried out before development of severe atrophy is capable to decrease the risk of stomach cancer. Conclusion. Proceedings and conclusions of consensus can become a cornerstone for development of new international gastritis classification.